Analysis of Ash Contents in Wheat Flour by The Gravimetric Method: Analisis Kadar Abu dalam Tepung Terigu dengan Metode Gravimetri - Elisabeth Kinanthi Pangestuti; Petrus Darmawan (Jurnal Kimia dan Rekayasa, 2021)
Wheat flour is flour derived from seeds wheat which goes through the process of washing, stripping the husks, milling and bleaching until it forms a smooth and white flour. Ash content is an inorganic substance in wheat flour that does not burn out and does not evaporate during the combustion process. Ash content can be used to evaluate the nutritional value of a food ingredient and show the total minerals contained in that material which can be toxic, where the higher the ash content, the worse the quality of the food ingredient. The maximum ash content in wheat flour as a food ingredient according to SNI 3751: 2018 is 0.70%. The determination of the ash content in wheat flour was carried out by the gravimetric method (SNI 3751: 2018), which is to digest the organic components of the sample at high temperature in the furnace without a flame until gray-white ash is formed and a constant weight is achieved. The results of the analysis of wheat flour showed that the ash content in sample A was 0.46%, sample B was 0.58%, sample C was 0.57%, and sample D was 0.63%. From the results obtained, the four samples of wheat flour based on their ash content met the SNI 3751: 2018 requirements. AbstrakTepung terigu merupakan tepung yang berasal dari biji gandum yang telah dicuci, dikupas sekamnya, digiling, dan diputihkan (bleaching) sampai terbentuk tepung terigu yang berwarna putih dan halus. Kadar abu merupakan zat anorganik di dalam tepung terigu yang tidak habis terbakar dan tidak menguap dalam proses pembakaran. Kadar abu dapat digunakan untuk mengevaluasi nilai gizi bahan pangan serta menunjukkan total mineral yang dapat bersifat toksik yang terkandung dalam bahan tersebut, dimana semakin tinggi kadar abu akan semakin buruk kualitas bahan pangan tersebut. Kadar abu maksimal pada tepung terigu sebagai bahan makanan menurut SNI 3751:2018 adalah sebesar 0,70%. Penentuan kadar abu dalam tepung terigu dilakukan dengan metode gravimetri (SNI 3751:2018), yaitu mendestruksi sampel pada suhu tinggi di dalam furnace tanpa terjadi nyala api sampai membentuk abu yang berwarna putih keabuan dan tercapainya bobot konstan. Hasil analisis tepung terigu pada sampel A didapatkan kadar abu sebesar 0,46%, sampel B sebesar 0,58%, sampel C sebesar 0,57%, dan sampel D sebesar 0,63%. Dari hasil yang didapatkan, keempat sampel tepung terigu tersebut berdasarkan kadar abunya memenuhi persyaratan SNI 3751:2018.